Response of soil nutrient dynamics and stoichiometric characteristics in blueberry to fertilization rates - Xianyong Wang; Xiaoli An; Na Lei; Delu Wang (PLoS ONE, 2025)
To accurately understand the fertilizer requirements of blueberries during various growth stages, this study utilized 7-year-old rabbiteye blueberry cultivar ‘Powderblue’ as the research material. Based on leaf ecological stoichiometry, combined with photosynthetic rate and leaf area, the theoretical nitrogen (N), phosphorus (P), and potassium (K) requirements were calculated every 10 days across four growth stages: flowering (S1), fruit setting (S2), young fruit development (S3), and fruit expansion (S4). Fertilization experiments with 1× (1F), 5× (5F), 10× (10F), and 15× (15F) of the theoretical nutrient demands were conducted during these four stages to investigate the effects of varying NPK application rates on soil nutrient content throughout the annual growth cycle. Results indicated that high fertilizer treatments significantly increased short-term soil N, P, and K availability; however, their concentrations decreased by day 10 post-application, indicating the necessity for topdressing at 10-day intervals to maintain nutrient effectiveness. Soil organic carbon and organic matter levels tended to increase on day 5 post-fertilization but generally decreased by day 10, with more pronounced declines observed in low-rate treatments (e.g., 1F). Soil stoichiometric ratios remained relatively stable across fertilizer gradients, suggesting that plants absorbed nutrients proportionally while maintaining a balance of residual nutrients. Blueberries exhibited higher N uptake compared to P and K across all stages, with the fruit expansion stage demonstrating the highest nutrient absorption rates—2.95 to 10.55 times (N), 3.05 to 6.53 times (P), and 2.77 to 8.54 times (K) those of the preceding stages. These findings underscore the necessity of prioritizing nitrogen (N) supply while dynamically adjusting phosphorus (P) and potassium (K) application ratios during each growth phase, particularly during the fruit expansion stage. Furthermore, balancing soil organic matter mineralization and accumulation is crucial for achieving synergistic regulation of nutrient use efficiency and soil health.